2005
DOI: 10.1016/j.bmcl.2005.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of structure–activity relationships for the ‘B-region’ of N-(4-t-butylbenzyl)-N′-[4-(methylsulfonylamino)benzyl]-thiourea analogues as TRPV1 antagonists

Abstract: The structure-activity relationships for the 'B-region' of N-(4-t-butylbenzyl)-N'-[4-(methylsulfonylamino)benzyl]thiourea analogues have been investigated as TRPV1 receptor antagonists. A docking model of potent antagonist 2 with the sensor region of TRPV1 is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Isocyanate 23 was synthesized accordingly to a reported procedure, starting from tert -butyl (4-(aminomethyl)­phenyl)­carbamate, which in turn was prepared as in ref . Isocyanate 34 was synthesized according to a previously reported procedure …”
Section: Methodsmentioning
confidence: 99%
“…Isocyanate 23 was synthesized accordingly to a reported procedure, starting from tert -butyl (4-(aminomethyl)­phenyl)­carbamate, which in turn was prepared as in ref . Isocyanate 34 was synthesized according to a previously reported procedure …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, mutagenesis studies within the TM3/4 region identified several key molecular determinants such as Tyr 511 , Ser 512 ,Met/Leu 547 , and Thr 550 that led to the proposed models of agonist and antagonist interactions with the vanilloidbinding pocket (Jordt and Julius, 2002;Chou et al, 2004;Gavva et al, 2004;Lee et al, 2005). Molecular determinants for proton activation have been reported to be present in the prepore loop, such as Glu 600 and Glu 648 (Jordt et al, 2000) and are different from those that constitute the vanilloidbinding pocket.…”
mentioning
confidence: 99%
“…As the model of Gavva et al is consistent with these observations, we adopted this structural model for the docking and visualization of some representative cinnamides reported here, with the purpose of showing plausible interactions of the antagonists with the TM3/4 helices, consistent with the 3D-QSAR models proposed here. The model was generated by building the TM3 and TM4 helical protein segments in α-helical conformation, with a loop connecting the helices, using the Biopolymer module of Insight II . This structural model 3 was also employed by Lee et al for docking and analyzing a different class of the TRPV1 antagonists, similar in size to the current set of ligands.…”
Section: Resultsmentioning
confidence: 99%